PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN KOMITE AUDIT TERHADAP AUDIT DELAY - FRANSISKA YUNINDA (2020)
This study was conducted to examine the effect of Company Size, Profitability, Audit Committee and KAP Reputation on Audit Delay. The dependent variable in this study is Company Size, Profitability and Audit Committee. The control variable in this study is KAP Reputation. This type of research is quantitative research using secondary data from the lease reports of manufacturing sector companies during the period 2014 to 2018 obtained from the Indonesia Stock Exchange (IDX). The sampling technique in this study used panel data and collected 63 samples. Testing the hypothesis in this study using Panel Data Regression Analysis with IBM SPSS version 22 with a significance level of 5% (0.05). The results showed that the Audit Committee had a significant effect on Audit Delay, but Company Size and Profitability had no effect on Audit Delay. Keywords: Audit Delay, Company Size, Profitability, Audit Committee